Household Economies of Scale in Consumption: Theory and Evidence - Nelson, Julie A. (Econometrica, 1988)
Household economies of scale (arising from the existence of househo ld public goods, increasing returns in household production, and/or bulk discounts) are incorporated into a utility-theoretic model of household demands. Individuals are assumed to be identical and symmetrically treated within households. Economies of scale parameters for five goods are estimated using the quadratic expenditu re system and data from the U.S. Consumer Expenditure Survey on expenditures by all-adult households. Results suggest the existence o f significant economies of scale in the consumption of all of the included goods, with economies being especially pronounced in the consumption of shelter. Copyright 1988 by The Econometric Society.